Study on the Mediating Effect of Intimate Relationship between Dyadic Coping and Quality of Life in Gynecological Cancer Patients' Couples - YE Huihui, GE Lina, ZANG Shuang, HU Shuang (Zhongguo quanke yixue, 2022)
BackgroundDyadic coping are associated with quality of life in gynecologic cancer patients, but the mechanism path of action is still unclear.ObjectiveTo explore the mechanism of intimate relationship between dyadic coping and quality of life in gynecological cancer patients.MethodsBy using a convenience-sampling method, 309 hospitalized gynecological cancer patients from Shengjing Hospital of China Medical University from May 2020 to February 2021 were selected as the research objects. The general data questionnaire was used to investigate the general data of patients, the Dyadic Coping Inventory was used to assess the dyadic coping under stress. The Chinese version of the Lock-Wallace Marriage (Love) Relationship Adjustment Scale was used to evaluate the quality of intimate relationships between couples, the The Chinese version of the World Health Organization Quality of Life-BREF Scale (including the four dimensions of physical health, mental health, social relations, and environment) was used to examine the quality of life of patients.ResultsA total of 320 questionnaires were distributed, 11 invalid questionnaires were excluded, and 309 valid questionnaires were returned, with an effective recovery rate of 96.56%. The average score of positive dyadic coping, negative dyadic coping and total score of dyadic coping for 309 patients were (48.2±7.4) , (8.3±1.4) , and (97.9±11.4) , respectively. The Chinese version of Locke-Wallace Marital (love) Adjustment and Prediction Test's mean score was (90.9±19.7) . The average score for the physical domain, psychological domain, social domain, and environment domain were (41.9±14.1) , (49.8±11.9) , (50.6±13.4) , and (47.8±9.9) , respectively. Multiple linear regression analysis showed that the total score of the Lock-Wallace Marital (love) Adjustment and Prediction Scale were significantly correlated with physical domain scores in gynecologic cancer patients (P<0.05) ; The Lock-Wallace Marital (love) Adjustment and Prediction Scale scores were associated with psychological domain scores in gynecologic cancer patients (P<0.05) ; The Lock-Wallace Marital (love) Adjustment and Prediction Scale scores were associated with social domain scores in gynecologic cancer patients (P<0.05) ; The total score of dyadic coping and Lock-Wallace Marital (love) Adjustment and Prediction Scale were significantly correlated with environment domain scores in gynecologic cancer patients (P<0.05) . The results of Structural Equation Model showed that the total score of dyadic coping positively predicted Lock-Wallace Marital (love) Adjustment and Prediction Scale (β=0.931, P<0.001) , Lock-Wallace Marital (love) Adjustment and Prediction Scale scores positively predicted the World Health Organization Quality of Life-BREF Scale scores (β=0.781, P=0.012) , and the total score of dyadic coping exerted no predictive effect on the World Health Organization Quality of Life-BREF questionnaire scores (β=0.112, P=0.688) .The results of the bootstrap sampling method (5 000 replicates) showed that the mediating effect of intimate relationship on the relationship between dyadic coping and quality of life was 0.727, accounting for 86.7% of the total effect.ConclusionGynecological cancer patients may have a relatively low level of dyadic coping, unsatisfactory intimate relationship, and poorer quality of life. The dyadic coping can indirectly predict the quality of life through intimate relationship was verified by structural equation modeling.